Politics and Gender Development: Dynamics of Women’s Representation in Legislative Institutions in Tuban Regency - Iswanto, Denny (SERUNAI, 2024)
Women's representation in legislative institutions is an important indicator in measuring political progress and gender development in a region. This study focuses on the development of women's representation in the legislative institution of Tuban Regency, as well as the political dynamics that influence the process. The main objectives of this study are to analyze changes in the quantity and quality of women's representation in legislative institutions and to identify factors that support and hinder women's political participation. Using a mixed approach, data were collected through in-depth interviews, surveys, and document analysis. The results show that although there has been an increase in the number of women elected, they still face challenges in actively participating and influencing policy. Local political culture factors, party support, and political education were found to have significant influences on women's success in politics. This study suggests the need for systematic efforts to overcome these obstacles and strengthen support for women, to achieve better gender equality in legislative institutions. These findings have important implications for policymakers, political parties, and the community in formulating more effective strategies to encourage women's political representation.